Architecture and Social Sustainability: Understanding the New Paradigm (Routledge, 2002)
Architecture and Social Sustainability shows how we can better design for stakeholder agency, serve historically marginalized populations, and further our theoretical thinking about sustainability writ large. With chapters exploring both the urban and the building scale, this volume examines the design of buildings and urban settings to illustrate how we can create more inclusive and equitable communities through broadening our design approach. Tracing how the professionalization of architecture and urban design has shut out stakeholder input, this book offers a range of methods and theoretical ideas to re-tool the design process for better social sustainability. The book illustrates these concepts through a series of case studies that have worked around systemic inequalities, recaptured stakeholder voices, and helped promote spatial and social justice. Case studies look at reparative urban and landscape design the United States, informal market structures in Nigeria, co-designed housing for low-income communities in India and Brazil, and participatory design for housing, schools, and healthcare facilities in Europe and the U.K. Essential reading for architects and urban designers seeking alternatives to conventional practice, as well as educators and students incorporating social sustainability as a foundational design concept, Architecture and Social Sustainability ties together design thinking and action to show architecture’s potential for social change. The Open Access version of this book, available at http://www.taylorfrancis.com, has been made available under a Creative Commons [Attribution-Non Commercial-No Derivatives (CC-BY-NC-ND)] 4.0 license.